Histological and immunohistochemical features of the ovarian malignant tumors with different histogenesis. - Savchenko, O. A. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Among neoplastic gynecologic diseases, ovarian cancer is in the top five in mortality, ranking fourth. These facts are explained, on the one hand, by the lack of specific clinical manifestations, which causes the diagnosis of the process in its later stages with often metastatic lesions. On the other hand, there is the problem of reliable verification of the diagnosis. The division of ovarian cancer into type 1 and type 2 indicates different patterns of ontogeny. The objective of the study is to improve the complex of differential diagnostic morphological criteria for the verification of benign, borderline and malignant ovarian tumors, based on the latest international classifications. Methods. A retrospective analysis of 169 ovarian epithelial tumors, including 37 cases of benign tumors, 120 cases of borderline tumors and 12 highly differentiated carcinomas of various histological types, included the evaluation of immunohistochemical features with subsequent statistical processing of the results obtained. Results. In all groups of epithelial tumors of the ovary, certain groups and differences of different histological features (changes in the structure of the cover epithelium, polymorphism of tumor cells) and features of immunophenotypes of the investigated tumors were revealed. These data make it possible to speak about the diagnostic value of each indicator for the investigated epithelial tumors of the ovaries. Сonclusion. Among the histological characteristics of importance were: epithelium cover, the degree of expression of polymorphism, the indicator of mitotic activity. Among the panel of immunohistochemical antibodies are the cytokeratin fractions (cytokeratin 7, cytokeratin 20), the nature of staining on Ki-67, p53, WT-1, EMA and CA-125.